Acceptability of HIV Vaccine - Efficacy Trials in Drug Users and Sexual Partners of HIV Infected Patients in Barcelona, Spain - Sanvisens, Arantza; Rivas, Inmaculada; Guerola, Rosa; Cobarsi, Patricia; Rall, Rayen; Fuster, Daniel; Romeu, Joan; Clotet, Bonaventura; Tor, Jordi; Muga, Robert (IntechOpen, 2011)
None